PENGARUH MODEL PEMBELAJARAN LEARNING STARTS WITH A QUESTION TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA KELAS V SD NEGERI BONTOKAMASE - Rexy Fernanda; Nasrah Nasrah; Anisa Anisa (Universitas Katolik Widya Karya Malang, 2023)
The type of research used is a quasi-quantitative experiment. This experimental research uses a quasi-experimental research design with nonequivalent control group design. This study aims to determine the effect of the Learning Starts With a Question learning model on student learning outcomes in fifth grade science learning at SD Negeri Bontokamase. From the test results, the Pretest value is 0.055 > 0.05 and the Post-test value is 0.073 > 0.05. From these tests, it can be concluded that the Pretest value is greater than 0.05 and the Post-test value is greater than 0.05. The homogeneity test results obtained Sig value α = 0.575, this means that the Sig value is greater than α (0.575 > 0.05) so that it can be concluded that the two groups are homogeneous. the hypothesis results obtained Sig (2.Tailed) = 0.000 meaning that H0 was rejected because Sig (2.Tailed) < α or (0.000 < 0.05). H1 is accepted because Sig (Tailed) > α or (0.575 > 0.05). In the T test analysis, Sig < table or (0.575 < 1.697). ). Based on the results of the study it can be concluded that there is a significant influence between learning taught using the Learning Starts With a Question model and conventional learning on science learning in fifth grade students of SD Negeri Bontokamase.